Effect of Self-Service Technology on Customer Satisfaction in Islamic Banks in Indonesia : FEBI UINSU Students - Nugraha, Agung; Harahap, Rahmat Daim; Syarvina, Wahyu (Ilomata International Journal of Management, 2024)
With the advancement of technology, particularly in the banking sector, innovations like ATMs and Mobile Banking have significantly evolved. However, there are accompanying challenges such as security vulnerabilities and network disruptions, which can lead to customer apprehension and dissatisfaction. This research aims to explore the impact of Digital Banking with Self-Service Technology (ATM and Mobile Banking) on Customer Satisfaction in Sharia Banks. The study employs a quantitative research approach with primary data collected through questionnaires from a sample of 50 respondents. Data analysis utilizes SPSS version 23. The findings indicate that both M-Banking and ATM services significantly influence customer satisfaction. Statistical tests, including partial and simultaneous tests, reveal significance levels < 0.05, underscoring the impact of M-Banking and ATM services on enhancing customer satisfaction. Implications from this research underscores the critical role of M-Banking and ATM services in shaping customer satisfaction within Sharia Banks. By addressing security concerns and optimizing network reliability, banks can enhance customer trust and loyalty. Insights from this study can guide banks in refining their digital strategies, improving service quality, and ultimately fostering stronger customer relationships in the digital banking era.